1992
DOI: 10.1557/proc-280-55
|View full text |Cite
|
Sign up to set email alerts
|

Some Comparisons of Ag Deposits on Ge and Si(111)

Abstract: Crystal growth and surface diffusion have been studied in the Ag/Ge(lll) system using UHV-SEM based techniques, biassed secondary electron imaging (b-SEI), micro-AES and RHEED. Ag was deposited through and past a mask of holes held close to the substrate at 300<Td< 775K. Under certain conditions, the Ag patches were observed to split into two regions corresponding to the √3×√3R30° (hereafter √3) and a lower coverage 4×4 structure, each of which were easily observable using b-SEI. These patch widths were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…It has been reported that the tensile strength of boron-free virgin E-glass fibres lies in the range from 3.1 to 3.8 GPa [2]. The reduced strength (below the pristine value) is generally considered to be a manifestation of surface flaws existing on the tested samples [20,21]. Since both samples have experienced an identical production, mechanical handling, and environmental history before testing, the results in Fig.…”
Section: Fibre Strength and Distributionmentioning
confidence: 99%
“…It has been reported that the tensile strength of boron-free virgin E-glass fibres lies in the range from 3.1 to 3.8 GPa [2]. The reduced strength (below the pristine value) is generally considered to be a manifestation of surface flaws existing on the tested samples [20,21]. Since both samples have experienced an identical production, mechanical handling, and environmental history before testing, the results in Fig.…”
Section: Fibre Strength and Distributionmentioning
confidence: 99%